(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless device portability and power efficiency are the two major challenges in modern device modelling. Voltage Controlled Oscillator (VCO) is one the most essential circuit used in wireless systems. From last decade, people want to be connected all the time using wireless communication devices. In addition, the demand for high bandwidth communication channels has exploded with the advent of the internet. Thanks to the high density available on integrated circuits, sophisticated digital modulation schemes can be employed to maximize the capacity of these channels. This has changed the design of wireless and wire line transceivers. We focus on the design of a critical sub-block: the voltage controlled oscillator (LC oscillator, VCO). We review the requirements for VCOs and evaluate the advantages and disadvantages of VCO. A new approach is proposed work is aimed to achieve the desired operating frequency, high stability. Power has become one of the most important paradigms for microprocessor & ASIC/SOC designs. Hence to have very low power consumption, this paper work is decided to implement using VLSI technology.